Management of Thoracic Insufficiency Syndrome in Patients With Jeune Syndrome Using the 70 mm Radius Vertical Expandable Prosthetic Titanium Rib. Issue 8 (December 2015) - O'Brien, Aaron; Roth, Megan K.; Athreya, Hariharan; Reinker, Kent; Koeck, William; Patil, Vishwas; Trevino, Hope; Simmons, James; Joshi, Ajeya P.; Smith, Melvin D.; Campbell, Robert M.
Abstract : Background: Jeune syndrome (JS) often results in lethal thoracic insufficiency syndrome. Since 1991, vertical expandable prosthetic titanium rib Dynamic PosteroLateral Expansion Thoracoplasty was used at our institution for treatment of JS. This study assesses the safety and efficacy of this procedure. Methods: Twenty-four JS patients were treated, 2 lost to follow-up, 17 with a minimum of 2-year follow-up retrospectively reviewed for clinical course: Assisted Ventilation Rate, respiratory rate, capillary blood gases, pulmonary function testings, and complications. Upright anteroposterior/lateral radiographs were measured for Cobb angle, kyphosis, lordosis, thoracic width, and thoracic/lumbar spinal height. Computed tomography scan lung volumes were obtained in 12 patients. Results: Mean age at initial implant was 23 months (7 to 62 mo) with an average 8.4 years (2.3 to 15.6 y) of follow-up. Average chest width increased from 121 to 168 mm at follow-up ( P <0.001). Preoperatively, 7/17 (41%) patients had scoliosis. The remainder developed scoliosis during treatment, 8 requiring additional implants. Thoracic and lumbar spinal height was normal preoperatively and stayed normal during treatment. Thoracic kyphosis/lumbar lordosis was stable. Average computed tomography scan total lung volumes increased 484 to 740 mm 3 ( P <0.001), and Assisted Ventilation Rate status tended to improve ( P =0.07). Average forced vital capacity was 34% predicted at first test and 27% predicted at last follow-up. Early demise after surgery was common with multisystem disease. Mean respiratory rate decreased from 35 to 24 bpm at last follow-up ( P <0.05). Survival rate of the 22 patients was 68%. Migration of the rib cradles/titanium slings occurred in 12 patients, superficial infections in 5 patients, deep infections in 4 patients, and wound dehiscence in 5 patients. Infection rate was 4.6% per procedure. Conclusions: The survival rate in JS with surgery was nearly 70% (compared with 70% to 80% mortality without treatment) with less ventilator dependence. Both C1 stenosis and scoliosis are common in JS. Spinal height in JS is normal. Complications are frequent, but tolerable in view of the clinical gains and increase in survival. Level of Evidence: Level IV—retrospective therapeutic case series.